Emergency Department Healthcare Providers’ Knowledge and Attitudes regarding Appropriate Indications for Indwelling Urinary Catheter Use - Tareq Al-Salamah; Alanoud Alessa; Hassan Aloraini; Fahad Abuguyan; Badr Aldawood; Fathima Fazrina Farook (Advances in Human Biology)
Introduction: Indwelling urinary catheters (IUCs) are frequently used in emergency departments (EDs), but many insertions lack clear indications, leading to potential overuse. This overuse contributes to catheter-associated urinary tract infections (CAUTIs), costing billions in preventable healthcare expenses. Campaigns such as Choosing Wisely and Centers for Disease Control and Prevention guidelines aim to reduce unnecessary IUC use, improve patient outcomes and prevent CAUTIs. Materials and Methods: A cross-sectional survey and retrospective chart review were conducted at an academic tertiary care centre. The survey targeted ED providers, including physicians and nurses, while the chart review encompassed all adult ED patients in 2022. The survey covered demographic information, self-reported understanding and attitudes towards urinary catheters, including clinical scenarios, to evaluate the knowledge of appropriate indications for IUC insertion. The data analysis was performed using NCSS software and involved t-tests or one-way analysis of variance to explore associations between sample characteristics and knowledge scores. The significance level for all analyses was set at P < 0.05. Results: A total of 96 of the 198 ED staff members participated in the survey. The confidence rate for knowledge of appropriate indications for IUC insertion was 100% among physicians and 97.8% among nurses. However, the results from the clinical scenarios in the survey showed that participants incorrectly answered in a range of 8%–75%. The mean scores of correct answers among consultants, residents and nurses were 65%, 67% and 66%, respectively. Conclusion: There is a considerable gap between ED healthcare providers’ subjective knowledge and attitudes and objective knowledge of appropriate IUC placement, which serves as a basis for an intervention to reduce the potential for inappropriate IUC insertion.